2019
DOI: 10.11648/j.jgo.20190704.11
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Causes and Factors Responsible for Maternal Mortality in a Tertiary Care Institute of Central Gujarat

Abstract: Maternal mortality is still a big health concern in developing world. The state of maternal health represents overall state of women's right in health, social and economic realms. If the causes of death can be addressed and are found to be preventable it indicates negligence on the part of government and the entities that have the power to implement the changes. To determine factors and causes of maternal mortality this retrospective observational study was conducted in the department of obstetrics and gynaeco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 9 publications
(10 reference statements)
3
3
0
Order By: Relevance
“…A study recently undertaken in Central Gujarat, India (2019) supports these results. The study reported that the largest number of maternal deaths (83.1%) occurred in the age group of 20-34 but the MMR increased significantly in women 35 years old and above [41]. These results confirm what has been found in studies carried out in the United States and a WHO multi-country Survey on Maternal and Newborn Health on pregnancy-related mortality that advanced maternal age predisposes women to adverse pregnancy outcomes [42,43].…”
Section: Discussionsupporting
confidence: 69%
“…A study recently undertaken in Central Gujarat, India (2019) supports these results. The study reported that the largest number of maternal deaths (83.1%) occurred in the age group of 20-34 but the MMR increased significantly in women 35 years old and above [41]. These results confirm what has been found in studies carried out in the United States and a WHO multi-country Survey on Maternal and Newborn Health on pregnancy-related mortality that advanced maternal age predisposes women to adverse pregnancy outcomes [42,43].…”
Section: Discussionsupporting
confidence: 69%
“…Also 2 cases were from Qena Governorate, they came to Sohag University Hospital and that was a waste of time. That is compatible with Kachhwaha and Jain (13) that showed maximum deaths occurred in patients with rural locality by 71% and Karlsen et al (14) who showed presence of differences between urban and rural areas especially in the poor countries. In addition woman's education in urban areas is higher than in rural areas and this is an important factor, where educated woman can determine the risks and complications early and usually aware about health services more than the illiterate woman.…”
Section: Discussionsupporting
confidence: 86%
“…In our study, the largest number of deaths occurred in the age group of 20-35, may be because those are the ages at which women are most likely to give birth, so efforts directed at this age group would most effectively reduce the number of deaths. According to Kachhwaha and Jain (13) a young pregnant women carries higher risk due to preeclampsia, cephalopelvic disproportion, uterine inertia and anemia. This is compatible with our study, in age group equal to or less than 35 there were 9 cases of preeclampsia and 6 cases of obstetric hemorrhage.…”
Section: Discussionmentioning
confidence: 99%
“…One of the major difficulties of implementing an obstetric audit program in low- income countries is the poor quality of data collected [15]. There are many sources of errors based on retrospective data recording and of interpretation, errors from disorganization in patients’ files, and errors of tallying and reporting.…”
Section: Discussionmentioning
confidence: 99%
“…Over 60% of low and middle income countries (LMICs) have a dysfunctional system of Civil Registration (CR), which is often regarded as the gold standard for producing reliable data on maternal deaths [14]. A study conducted in India revealed a significant underreporting of maternal deaths [15]. This is very crucial as each unrecorded maternal death is a missed opportunity to prevent similar deaths in the future [16].…”
Section: Introductionmentioning
confidence: 99%